Annemarie Sorescu-Marinković, Thede Kahl, Biljana Sikimić (eds.): Boyash Studies: Researching "Our People": Berlin: Frank & Timme, 2021, 462 s., ISBN 978-3-7329-0694-9 - Kubaník, Pavel (Romano džaniben, 2022)
RECENZE